Design and control of a 3D robot-assisted rehabilitation device for post-stroke - Sidek, Shahrul Na'im; Fatai, Sado (Springer, 2021)
With the ever-increasing population of stroke patients requiring rehabilitation therapy compared with the few available therapists, what is now crucial is an adaptive system that can complement closely the role of an expert therapist by sensing the patients’ muscle tone, physical recovery condition, or sensorimotor control performance to specify appropriate therapy and to provide an assessment. A “high-level” adaptive hybrid impedance controller based on Modified Ashworth Scale (MAS) assessment criteria for rehabilitation of the upper extremity of poststroke patients was therefore proposed and discussed in this chapter. An end-effectorbased 3 degree-of-freedom (3-DOF) rehabilitation platform was developed with the proposed control strategy with the emphasis on proper joint coordination and control to actualize effective trajectory tracking and consequently effective therapy.